KAJIAN PENGENDALIAN PERSEDIAAN OBAT DI INSTALASI FARMASI DINAS KESEHATAN KABUPATEN “X” JAWA TENGAH - Siti Munisih; Maria Caecilia N. Setiawati H; FX Sulistiyanto WS (Dian Nuswantoro Semarang, 2022)
ABC critical index analysis is a combination of ABC analysis which includes ABC analysis of value in use and ABC analysis of investment value. The ABC analysis method is a method of making classifications based on the set of values from the highest to the lowest value and is divided into 3 major groups called group A (high investment value), B (medium investment value), and C (low investment value).The purpose of this study was to determine the compatibility, and realization and provide an evaluation of the planning for the use of drugs using the ABC method in the pharmaceutical installation health department of “X” district, Central Java. The sampling technique used in this research is purposive sampling where the sample is taken according to the sample criteria.Data on Usage Reports and Drug Request Sheets for all UPTD Public Health Centers of “X” Regency from January - December 2019 and January - December 2020. In the use of drugs in 2019 there were 343 types of drugs, consisting of group A as many as 64 drug items (18.66%) with a procurement cost of Rp. 3,647,892,228.00,- (74.83%), group B as many as 98 drug items (28.57%) with a cost of Rp. 980.902.019.40,- (20.12%). While those included in group C were 181 items (52.77%) with a cost of Rp. 246.216,758.60,- (5.29%). The results show that the budget needed for drug procurement in 2019 is IDR 4,875,011,006,00, - in 2020 there are 487 types of drugs, group A consists of 50 drug items (10.27%) with procurement costs of IDR 5,167,276,066 ,00,- (74.38%). A total of 104 drug items were included in group B (21.36%) with a cost of Rp. 1,392,954,441.00 (34.1%). While those included in group C were 333 items (68.38%) with a cost of Rp. 387,321,439.00, - (8.41%). The results show that the budget needed for drug procurement in 2020 is IDR 6,974,551,946,00,-. Keywords: compatibility, realization, evaluation, ABC